Layered oxide material with valence change of transition metal and oxygen at same time, preparation method and application
By using layered oxide materials with transition metal and oxygen devalence simultaneously in the positive electrode material of sodium ion battery, the problems of low specific capacity and unstable oxygen devalence are solved, and high specific capacity and stability are improved, which is suitable for high energy density applications of sodium ion batteries.
Patent Information
- Application Number
- CN202411874227.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-18
AI Technical Summary
The specific capacity of the existing sodium ion battery positive electrode material is low, which limits the energy density of the battery, and the stability and reversibility of oxygen devalence are insufficient, affecting the overall performance of the material.
A layered oxide material with transition metal and oxygen devalence simultaneously is used to achieve high specific capacity through the synergistic valence state of transition metal and oxygen, and the stability of oxygen devalence is improved through structural design and appropriate preparation methods. The specific material chemical formula is NaxMgaMnbMcNdO2, M is Ni, Cu or Fe, N is Ti, 0.6≤x≤0.74, 0.2≤a≤0.29, 0.48≤b≤0.6, 0.1≤c≤0.15, 0.1≤d≤0.15, a+b+c+d=1.
It has achieved the stability improvement of high specific capacity and oxygen devalence, effectively improving the comprehensive performance of layered oxide positive electrode, and is suitable for sodium ion batteries.
Smart Images

Figure CN119852385A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a layered oxide material in which transition metal and oxygen change valence simultaneously, a preparation method and application thereof. Background Art
[0002] As one of the most important energy storage technologies, lithium-ion batteries are widely used in portable electronic devices, electric vehicles and other fields. However, as lithium resources are unevenly distributed and scarce, the price of lithium-ion batteries is easily affected by the supply side. Sodium-ion batteries are similar to lithium-ion batteries, but sodium resources are more abundant and the cost is lower. Sodium-ion batteries have received more and more attention. The development of sodium-ion batteries with high energy density and excellent cycle life can achieve functional complementarity with lithium-ion batteries, and has good application prospects in the field of large-scale energy storage.
[0003] The energy density of sodium-ion batteries is one of the key factors that determine whether they can be used in practice. The low specific capacity of the cathode materials of sodium-ion batteries limits the energy density of the batteries. Traditional layered transition metal oxide materials have two-dimensional sodium ion diffusion channels and simple synthesis processes, and have been widely studied as cathode materials for sodium-ion batteries. At present, based on layered oxides with variable valence of transition metal elements, transition metals are considered to be the only charge compensation in the electrochemical reaction process. Therefore, the specific capacity of the cathode material is limited by the variable valence transition metal content, and the specific capacity is difficult to increase significantly in a short period of time. Therefore, exploring high specific capacity cathode materials is of great significance for realizing large-scale application of sodium-ion batteries.
[0004] Recent studies have found that in some layered transition metal oxides, oxygen can also participate in the electrochemical reaction process. Therefore, layered oxides based on the dual redox reaction of transition metals and lattice oxygen have high specific capacity and are the preferred positive electrode materials for the next generation of high specific energy sodium ion batteries. Although some studies have focused on layered oxide materials in which transition metals and lattice oxygen change valence at the same time, how to improve the stability and reversibility of oxygen valence change through appropriate structural design and preparation methods so that these materials can perform optimally in sodium ion batteries is still a technical problem that needs to be solved. Summary of the invention
[0005] The purpose of the present invention is to provide a layered oxide material with simultaneous valence change of transition metal and oxygen and its preparation method and use, so as to solve the shortcomings of existing sodium ion batteries in terms of energy density. The material can achieve high specific capacity through the synergistic valence state of transition metal and oxygen, and improve the stability of oxygen valence change, thereby effectively improving the comprehensive performance of the layered oxide positive electrode.
[0006] To achieve the above object, the technical solution of the present invention is as follows: a layered oxide material in which transition metal and oxygen change valence simultaneously, and its chemical formula is:
[0007] Na x Mg a Mn b M c N d O2, M is Ni, Cu or Fe, N is Ti; 0.6≤x≤0.74, 0.2≤a≤0.29,
[0008] 0.48≤b≤0.6, 0.1≤c≤0.15, 0.1≤d≤0.15, a+b+c+d=1;
[0009] When the layered oxide material is used as a positive electrode material for a sodium ion battery, transition metal ions and oxygen ions with electrochemical activity simultaneously gain and lose electrons during the charge and discharge process, thereby achieving a coordinated valence change of the transition metal ions and the oxygen ions.
[0010] Further, in a specific embodiment, the layered oxide material in which the transition metal and oxygen change valence simultaneously as described above may be: Na 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 O2、Na 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 O2 or Na 2 / 3Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 O2.
[0011] In a specific embodiment, the present invention provides a method for preparing the layered oxide material in which the transition metal and oxygen are simultaneously valence-changed, and the preparation method is a solid phase method, comprising:
[0012] The required stoichiometric amounts of sodium carbonate or sodium nitrate, magnesium oxide, manganese dioxide, oxides or hydroxides of M and N are mixed in proportion to form a precursor, wherein M is one or more of Ni, Cu or Fe, and N is Ti;
[0013] The precursors are uniformly mixed by a grinding method to obtain precursor powder;
[0014] Pre-sintering the precursor powder at 300-500° C. for 4-6 hours;
[0015] Take out the pre-sintered product, grind it thoroughly, and then sinter it at 800-1100℃ for 12-24h;
[0016] The heat-treated product is ground to obtain the layered oxide material.
[0017] Further, in a specific embodiment, the preparation method (solid phase method) of the layered oxide material in which the transition metal and oxygen simultaneously change valence as described above, wherein the precursor is a mixture of oxides or hydroxides of Na2CO3 or NaNO3, MgO, MnO2, M and N according to the molar ratio of each element in the layered oxide material and the required stoichiometric ratio, wherein M is one or more of Ni, Cu or Fe, and N is Ti.
[0018] Furthermore, in a specific embodiment, the preparation method (solid phase method) of the layered oxide material in which the transition metal and oxygen simultaneously change valence as described above, wherein, after obtaining the precursor powder, the precursor powder is pre-sintered in a muffle furnace at 500°C for 5 hours, taken out and fully ground, and then sintered again in a muffle furnace at 950°C for 15 hours.
[0019] In a specific embodiment, the present invention provides another method for preparing the layered oxide material in which the transition metal and oxygen are simultaneously valence-changed, and the preparation method is a sol-gel method, comprising:
[0020] Sodium acetate or sodium sulfate, acetate, nitrate or sulfate containing magnesium, manganese, doping elements M and N are dissolved in water or ethanol according to the molar ratio of each element in the layered oxide material and mixed into a precursor solution according to a stoichiometric ratio; M is specifically one or more of Ni, Cu or Fe, and N is Ti;
[0021] Stirring at 60°C to 100°C, adding a proper amount of chelating agent, and evaporating to dryness to form a precursor gel;
[0022] The precursor gel is placed in a crucible and pre-fired in an air atmosphere at 300° C. to 500° C. for 4 to 6 hours;
[0023] Then heat treat at 800℃~1100℃ for 12~24 hours;
[0024] The heat-treated product is fully ground to obtain the layered oxide material.
[0025] Further, in a specific embodiment, in the method for preparing the layered oxide material with simultaneous valence change of transition metal and oxygen (sol-gel method) as described above, the amount of sodium acetate or sodium sulfate used is 100wt% to 108wt% of the stoichiometric amount of the required sodium.
[0026] Further, in a specific embodiment, in the method for preparing the layered oxide material with simultaneous valence change of transition metal and oxygen (sol-gel method) as described above, the chelating agent is citric acid with a stoichiometric ratio of 100%-200% molar ratio of all salts.
[0027] The present invention further provides the use of the layered oxide material in which the transition metal and oxygen change valence simultaneously, and uses the layered oxide material as a positive electrode material for a sodium ion battery.
[0028] In a specific embodiment, the layered oxide material in which the transition metal and oxygen change valence simultaneously is mixed with a conductive agent and a binder in proportion, uniformly coated on a current collector aluminum foil, and cut into a positive electrode sheet of a sodium ion battery after drying.
[0029] Furthermore, the mass ratio of the layered oxide material powder in which the transition metal and oxygen change valence simultaneously to the conductive agent and the binder is 8:1:1.
[0030] Furthermore, the conductive agent may be carbon nanotubes, and the binder may be PVDF.
[0031] The beneficial effects of the present invention are as follows:
[0032] 1) The present invention utilizes the synergistic valence change of transition metals and oxygen, and takes into account the characteristics of different elements forming chemical bonds with oxygen. Mg mainly activates the valence change of oxygen, Ni, Cu or Fe provide sufficient charge compensation as transition metal valence change, and Ti plays a role in stabilizing the structure as an electrochemically inert element, which not only achieves a high specific capacity, but also improves the stability of the material structure, thereby effectively improving the comprehensive performance of the layered oxide positive electrode.
[0033] 2) Pre-sintering at 300-500°C during material preparation can make the reaction more complete, ensure the purity of the synthetic material, and reduce the content of impurities such as MgO. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 XRD pattern of O2;
[0035] Figure 2 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1SEM photo of O2;
[0036] Figure 3 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 The charge and discharge curve of O2 at 0.1C rate;
[0037] Figure 4 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 Cycling performance diagram of O2 at 0.2C rate;
[0038] Figure 5 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 XRD pattern of O2;
[0039] Figure 6 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 SEM photo of O2;
[0040] Figure 7 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 The charge and discharge curve of O2 at 0.1C rate;
[0041] Figure 8 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 Cycling performance diagram of O2 at 0.2C rate;
[0042] Fig. 9 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 XRD pattern of O2;
[0043] Fig.10 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 SEM photo of O2;
[0044] Fig.11 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 The charge and discharge curve of O2 at 0.1C rate;
[0045] Fig.12 The P2-type layered oxide material Na prepared in the embodiment of the present invention has a transition metal and oxygen valence change at the same time. 2 / 3 Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 Cycling performance diagram of O2 at 0.2C rate. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0047] Embodiment 1:
[0048] This embodiment provides a P2-type layered oxide material in which transition metal and oxygen change valence simultaneously. The chemical formula of the P2-type layered oxide material is: Na x Mg a Mn b M c N d O2;
[0049] Wherein, M is Ni, Cu or Fe, and N is Ti;
[0050] The x, a, b, c, and d are respectively the molar percentages of the corresponding elements; wherein 0.6≤x≤0.74, 0.2≤a≤0.29, 0.48≤b≤0.6, 0.1≤c≤0.15, 0.1≤d≤0.15, and a+b+c+d=1.
[0051] Exemplary specific materials may be: Na 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 O2、Na 2 / 3Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 O2 or Na 2 / 3 Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 O2, etc. Among them, the molar amount of Ni, Cu, Fe or Ti can be appropriately adjusted within the ratio range of 0.1-0.15, and the molar amount of Mg and Mn elements can be appropriately adjusted accordingly, and the performance of the layered oxide material remains basically unchanged.
[0052] The P2-type layered oxide material of the present invention utilizes the synergistic valence change effect of transition metals and oxygen, and takes into account the characteristics of different elements forming chemical bonds with oxygen. On the one hand, it achieves a high specific capacity, and on the other hand, it improves the stability of oxygen valence change, thereby effectively improving the comprehensive performance of the layered oxide positive electrode, and has a good application prospect in the field of sodium ion batteries.
[0053] The preparation method for obtaining the material is described below.
[0054] Embodiment 2:
[0055] This embodiment provides a method for preparing a P2-type layered oxide material in which a transition metal and oxygen are simultaneously valence-changed, specifically a solid phase method, comprising:
[0056] Mixing the required stoichiometric amounts of sodium carbonate or sodium nitrate, magnesium oxide, manganese dioxide, oxides or hydroxides of M and N into a precursor in a required stoichiometric ratio according to the molar ratio of each element in the layered oxide material, wherein M is Ni, Cu or Fe, and N is Ti;
[0057] The precursors are uniformly mixed by a grinding method to obtain precursor powder;
[0058] The precursor powder is placed in a muffle furnace and sintered at 300-500° C. for 4-6 hours;
[0059] Take out and grind thoroughly, then sinter at 800-1100℃ for 12-24h;
[0060] The heat-treated product is fully ground to obtain the layered oxide material.
[0061] The preparation method of the P2-type layered oxide material provided in this embodiment can be used to prepare the P2-type layered oxide material in which the transition metal and oxygen are simultaneously valence-changed as described in the above-mentioned embodiment 1. The method provided in this embodiment is simple and easy to implement, low in cost, and the materials used are safe and non-toxic, and is suitable for large-scale manufacturing applications.
[0062] Embodiment three:
[0063] This embodiment provides a method for preparing a P2-type layered oxide material in which a transition metal and oxygen are simultaneously valence-changed, specifically a sol-gel method, comprising:
[0064] Sodium acetate or sodium sulfate with a stoichiometric amount of 100 wt% to 108 wt% of the required sodium, acetate, nitrate or sulfate containing magnesium, manganese, and doping elements M and N are dissolved in water or ethanol according to the molar ratio of each element in the layered oxide material and mixed into a precursor solution according to the required stoichiometric ratio; M is specifically Ni, Cu or Fe, and N is Ti;
[0065] Stirring at 60° C. to 100° C., adding a proper amount of a chelating agent, and evaporating to dryness to form a precursor gel; the chelating agent can be citric acid in a stoichiometric amount of 100% to 200% molar ratio of all salts;
[0066] The precursor gel is placed in a crucible and pre-fired in an air atmosphere at 300° C. to 500° C. for 4 to 6 hours;
[0067] Then heat treat at 800℃~1100℃ for 12~24 hours;
[0068] The heat-treated product is fully ground to obtain the layered oxide material.
[0069] The preparation method of the P2-type layered oxide material provided in this embodiment can be used to prepare the P2-type layered oxide material in which the transition metal and oxygen are simultaneously valence-changed as described in the above-mentioned embodiment 1. The method provided in this embodiment is simple and easy to implement, low in cost, and the materials used are safe and non-toxic, and is suitable for large-scale manufacturing applications.
[0070] Embodiment 4:
[0071] In this embodiment, the P2-type layered oxide material in which the transition metal and oxygen are simultaneously valence-changed is prepared by the solid phase method described in the above-mentioned embodiment 2, and includes:
[0072] Na2CO3 (analytical pure), MgO (analytical pure), CuO (analytical pure), MnO2 (analytical pure), and TiO2 (analytical pure) were mixed in the required stoichiometric ratio; the mixture was ground in an agate mortar for half an hour to obtain a precursor; the precursor was pressed into a tablet and transferred to an Al2O3 crucible, and treated in a muffle furnace at 500°C for 5 hours; the precursor was taken out, ground, pressed into a tablet again, and transferred to an Al2O3 crucible, and treated in a muffle furnace at 950°C for 15 hours to obtain the material Na 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 O2, its X-ray powder diffraction (XRD) spectrum can be found in Figure 1 , from the XRD spectrum, Na 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 The crystal structure of O2 is a P2-type layered structure. Figure 2 The scanning electron microscope (SEM) photo of this embodiment is given in FIG. 1 . It can be seen from the SEM photo that the Na 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 O2 is a bulk material.
[0073] The layered oxide material prepared above is used as the active material of the battery positive electrode material for the preparation of sodium ion batteries. The specific steps are: 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 O2 powder, conductive agent (such as carbon nanotubes), and binder (such as PVDF) are fully mixed in a mass ratio of 8:1:1. The slurry is evenly coated on the current collector aluminum foil in a room temperature dry environment, dried at 120°C for 10 hours under vacuum conditions, cut into pole pieces and transferred to a glove box for standby use. The assembly of the simulated battery is carried out in an Ar atmosphere glove box, with metallic sodium as the counter electrode and NaClO4 / ethylene carbonate:propylene carbonate = 1:1, 5% fluoroethylene carbonate (EC:PC = 1:1, 5% FEC) solution as the electrolyte, assembled into a CR2032 button cell.
[0074] Use constant current charge and discharge mode, test results see Figure 3 and Figure 4 . Figure 3This is the charge and discharge curve of the material at a rate of 0.1C. The specific capacity of the material is 200mAh / g; Figure 4 The material has a cycling performance of 0.2C rate and a capacity retention rate of 97% after 50 cycles, which indicates that it has excellent comprehensive electrochemical performance.
[0075] Embodiment five:
[0076] In this embodiment, the P2-type layered oxide material in which the transition metal and oxygen are simultaneously valence-changed is prepared by the solid phase method described in the above-mentioned embodiment 2, and includes:
[0077] Na2CO3 (analytical pure), MgO (analytical pure), Fe2O3 (analytical pure), MnO2 (analytical pure), and TiO2 (analytical pure) were mixed in the required stoichiometric ratio; the mixture was ground in an agate mortar for half an hour to obtain a precursor; the precursor was pressed into tablets and transferred to an Al2O3 crucible, and treated in a muffle furnace at 500°C for 5 hours; the precursor was taken out, ground, pressed into tablets again, transferred to an Al2O3 crucible, and treated in a muffle furnace at 950°C for 15 hours to obtain the material Na 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 O2, its X-ray powder diffraction (XRD) spectrum can be found in Figure 5 , from the XRD spectrum, Na 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 The crystal structure of O2 is a P2-type layered structure. Figure 6 The scanning electron microscope (SEM) photo of this embodiment is given in FIG. 1 . It can be seen from the SEM photo that the Na 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 O2 is a bulk material.
[0078] The layered oxide material prepared above is used as the active material of the battery positive electrode material for the preparation of sodium ion batteries. The specific steps are: 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1O2 powder, conductive agent (such as carbon nanotubes), and binder (such as PVDF) are fully mixed in a mass ratio of 8:1:1. The slurry is evenly coated on the current collector aluminum foil in a room temperature dry environment, dried at 120°C for 10 hours under vacuum conditions, cut into pole pieces and transferred to a glove box for standby use. The assembly of the simulated battery is carried out in an Ar atmosphere glove box, with metallic sodium as the counter electrode and NaClO4 / ethylene carbonate:propylene carbonate = 1:1, 5% fluoroethylene carbonate (EC:PC = 1:1, 5% FEC) solution as the electrolyte, assembled into a CR2032 button cell.
[0079] Use constant current charge and discharge mode, test results see Figure 7 and Figure 8 . Figure 7 This is the charge and discharge curve of the material at a rate of 0.1C. The specific capacity of the material is 215mAh / g; Figure 8 The material has a cycling performance of 0.2C rate and a capacity retention rate of 98% after 50 cycles, which indicates that it has excellent comprehensive electrochemical performance.
[0080] Embodiment six:
[0081] In this embodiment, the P2-type layered oxide material in which the transition metal and oxygen are simultaneously valence-changed is prepared by the solid phase method described in the above-mentioned embodiment 2, and includes:
[0082] Mix NaNO3 (analytical pure), MgO (analytical pure), NiO or Ni(OH)2 (analytical pure), MnO2 (analytical pure), and TiO2 (analytical pure) in the required stoichiometric ratio; grind in an agate mortar for half an hour to obtain a precursor; press the precursor into a tablet and transfer it to an Al2O3 crucible, and treat it in a muffle furnace at 500°C for 5 hours; take it out, grind it, press it into a tablet again, transfer it to an Al2O3 crucible, and treat it in a muffle furnace at 950°C for 15 hours to obtain the material Na 2 / 3 Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 O2, its X-ray diffraction (XRD) spectrum can be found at Fig. 9 , from the XRD spectrum, Na 2 / 3 Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 The crystal structure of O2 is a P2-type layered structure. Fig.10 The scanning electron microscope (SEM) photo of this embodiment is given in FIG. 1 . It can be seen from the SEM photo that the Na 2 / 3 Mg0.23 Ni 0.1 Mn 0.57 Ti 0.1 O2 is a bulk material.
[0083] The layered oxide material prepared above is used as the active material of the battery positive electrode material for the preparation of sodium ion batteries. The specific steps are: 2 / 3 Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 O2 powder, conductive agent (such as carbon nanotubes), and binder (such as PVDF) are fully mixed in a mass ratio of 8:1:1. The slurry is evenly coated on the current collector aluminum foil in a room temperature dry environment, dried at 120°C for 10 hours under vacuum conditions, cut into pole pieces and transferred to a glove box for standby use. The assembly of the simulated battery is carried out in an Ar atmosphere glove box, with metallic sodium as the counter electrode and NaClO4 / ethylene carbonate:propylene carbonate = 1:1, 5% fluoroethylene carbonate (EC:PC = 1:1, 5% FEC) solution as the electrolyte, assembled into a CR2032 button cell.
[0084] Use constant current charge and discharge mode, test results see Fig.11 and Fig.12 . Fig.11 This is the charge and discharge curve of the material at a rate of 0.1C. The specific capacity of the material is 185mAh / g; Fig.12 The material has a cycling performance of 0.2C rate and a capacity retention rate of 97% after 50 cycles, which indicates that it has excellent comprehensive electrochemical performance.
[0085] The layered oxide material in which the transition metal and oxygen change valence simultaneously provided by the embodiment of the present invention utilizes the synergistic valence change of the transition metal and oxygen, and takes into account the characteristics of different elements forming chemical bonds with oxygen. On the one hand, it achieves a high specific capacity, and on the other hand, it improves the stability of the oxygen valence change, thereby effectively improving the comprehensive performance of the layered oxide positive electrode. At the same time, the preparation method is simple, and it has good application prospects in the field of sodium ion batteries.
[0086] Those skilled in the art will readily conceive of other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. Thus, if these variations and use adaptations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and use adaptations.
[0087] The above embodiments are merely illustrative of the present invention, and the present invention may also be implemented in other specific ways or other specific forms without departing from the gist or essential features of the present invention. Therefore, the described embodiments should be considered illustrative rather than restrictive in any respect. The scope of the present invention should be described by the appended claims, and any changes equivalent to the intent and scope of the claims should also be included within the scope of the present invention.
Claims
1. A layered oxide material in which transition metal and oxygen change valence simultaneously, characterized in that: Its chemical formula is: Na x Mg a Mn b M c N d O2, M is Ni, Cu or Fe, N is Ti; 0.6≤x≤0.74, 0.2≤a≤0.29, 0.48≤b≤0.6, 0.1≤c≤0.15, 0.1≤d≤0.15, a+b+c+d=1; When the layered oxide material is used as a positive electrode material for a sodium ion battery, transition metal ions and oxygen ions with electrochemical activity simultaneously gain and lose electrons during the charge and discharge process, thereby achieving a coordinated valence change of the transition metal ions and the oxygen ions.
2. The layered oxide material in which the transition metal and oxygen are simultaneously changed in valence according to claim 1, characterized in that: The layered oxide material can be: Na 2 / 3 Mg 0.23 Cu 0.1 Mn 0.57 Ti 0.1 O2、Na 2 / 3 Mg 0.28 Fe 0.1 Mn 0.52 Ti 0.1 O2 or Na 2 / 3Mg 0.23 Ni 0.1 Mn 0.57 Ti 0.1 O2.
3. A method for preparing a layered oxide material in which the transition metal and oxygen are simultaneously valence-changed according to claim 1 or 2, characterized in that: The preparation method is a solid phase method, comprising: The required stoichiometric amounts of sodium carbonate or sodium nitrate, magnesium oxide, manganese dioxide, oxides or hydroxides of M and N are mixed in proportion to form a precursor, wherein M is Ni, Cu or Fe, and N is Ti; The precursors are uniformly mixed by a grinding method to obtain precursor powder; Pre-sintering the precursor powder at 300-500° C. for 4-6 hours; Take out the pre-sintered product, grind it thoroughly, and then sinter it at 800-1100℃ for 12-24h; The heat-treated product is ground to obtain the layered oxide material.
4. The method for preparing a layered oxide material in which transition metal and oxygen change valence simultaneously as claimed in claim 3, characterized in that: The precursor is a mixture of oxides or hydroxides of Na2CO3 or NaNO3, MgO, MnO2, M and N in a desired stoichiometric ratio according to the molar ratio of each element in the layered oxide material, wherein M is Ni, Cu or Fe, and N is Ti.
5. The method for preparing a layered oxide material in which transition metal and oxygen change valence simultaneously as claimed in claim 3, characterized in that: After the precursor powder is obtained, the precursor powder is sintered in a muffle furnace at 500° C. for 5 hours, taken out and fully ground, and then sintered again in a muffle furnace at 950° C. for 15 hours.
6. A method for preparing a layered oxide material in which the transition metal and oxygen are simultaneously valence-changed according to claim 1 or 2, characterized in that: The preparation method is a sol-gel method, comprising: Sodium acetate or sodium sulfate, acetate, nitrate or sulfate containing magnesium, manganese, doping elements M and N are dissolved in water or ethanol according to the molar ratio of each element in the layered oxide material and mixed into a precursor solution according to a stoichiometric ratio; M is specifically Ni, Cu or Fe, and N is Ti; Stirring at 60°C to 100°C, adding a proper amount of chelating agent, and evaporating to dryness to form a precursor gel; The precursor gel is placed in a crucible and pre-fired in an air atmosphere at 300° C. to 500° C. for 4 to 6 hours; Then heat treat at 800℃~1100℃ for 12~24 hours; The heat-treated product is fully ground to obtain the layered oxide material.
7. The method for preparing a layered oxide material in which transition metal and oxygen change valence simultaneously according to claim 6, characterized in that: The amount of sodium acetate or sodium sulfate used is 100 wt% to 108 wt% of the stoichiometric amount of sodium required.
8. The method for preparing a layered oxide material in which transition metal and oxygen change valence simultaneously as claimed in claim 6, characterized in that: The chelating agent uses citric acid in a stoichiometric amount of 100% to 200% molar ratio of all salts.
9. Use of the layered oxide material with simultaneous valence changes of transition metal and oxygen as claimed in claim 1 or 2, characterized in that: It is used as the positive electrode material for sodium-ion batteries.
10. Use of the layered oxide material in which the transition metal and oxygen are simultaneously valence-changed as claimed in claim 9, characterized in that: The layered oxide material in which the transition metal and oxygen change valence simultaneously is mixed with a conductive agent and a binder in proportion, and then evenly coated on a current collector aluminum foil, and then cut into a positive electrode sheet of a sodium ion battery after drying.
11. Use of the layered oxide material in which the transition metal and oxygen are simultaneously valence-changed as claimed in claim 10, characterized in that: The mass ratio of the layered oxide material powder in which the transition metal and oxygen change valence simultaneously to the conductive agent and the binder is 8:1:
1.
12. Use of the layered oxide material in which the transition metal and oxygen are simultaneously valence-changed as claimed in claim 10, characterized in that: The conductive agent may be carbon nanotubes, and the binder may be PVDF.